2011
DOI: 10.1002/humu.21545
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted posttranscriptional regulation of the cystic fibrosis transmembrane conductance regulator (CFTR) by a 5′UTR mutation is associated with a cftr-related disease

Abstract: Cystic fibrosis (CF) is characterised as a single-gene disorder with a simple, autosomal recessive mode of inheritance. However, translation of CFTR genotype into CF phenotype is influenced by nucleotide sequence variations at multiple genetic loci, and individuals heterozygous for CFTR mutations are predisposed to a range of CFTR-related conditions, such as Disseminated Bronchiectasis. CF disease severity and CFTR-related conditions are more akin to complex, multifactorial traits, which are increasingly being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…However, similar to the luciferase constructs, the +142T may generate an uORF that encodes a 73 aa out of frame peptide that competes with the translation of wild type GCH1 initiated by the pAUG. A model in which a mixture of wild type and truncated peptides are generated in a competitive manner due to creation of novel uAUGs has been reported in human diseases ranging from a predisposition to cancer [31] to bronchiectasis [32] and bipolar depression [33]. Our study expands this list to include dystonia by revealing that the +142C>T GCH1 5’UTR substitution detected in DRD patients is a functional mutation that reduces translational efficiency and likely leads to reduced wild type GCH1 protein levels, underlying manifestation of DRD.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to the luciferase constructs, the +142T may generate an uORF that encodes a 73 aa out of frame peptide that competes with the translation of wild type GCH1 initiated by the pAUG. A model in which a mixture of wild type and truncated peptides are generated in a competitive manner due to creation of novel uAUGs has been reported in human diseases ranging from a predisposition to cancer [31] to bronchiectasis [32] and bipolar depression [33]. Our study expands this list to include dystonia by revealing that the +142C>T GCH1 5’UTR substitution detected in DRD patients is a functional mutation that reduces translational efficiency and likely leads to reduced wild type GCH1 protein levels, underlying manifestation of DRD.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that predisposition to melanoma can be caused by mutations that introduce a uORF into the 5′ leader sequence of the mRNA encoding the cyclin-dependent kinase inhibitor protein ( CDKN2A ) [95], [96]. Other examples of human diseases associated with mutations that create a uORF include familial hypercholesterolemia (low-density lipoprotein receptor gene; LDLR ) [97], cystic fibrosis ( CFTR ) [98], congenital hyperinsulinism (potassium inwardly-rectifying channel, subfamily J, member 11; KCNJ11 ) [99], rhizomelic chondrodysplasia punctata (peroxisomal biogenesis factor 7; PEX7 ) [100], proopiomelanocortin deficiency syndrome (proopiomelanocortin; POMC ) [101], levodopa-responsive dystonia (guanosine triphosphate cyclohydrolase I; GCH1 ) [102], and juvenile hemochromatosis (hepcidin; HAMP) [103] (Table 1). Although the majority of the polymorphisms/mutations referred to here that create a uORF have been experimentally tested for their influence on translation, in the case of LDLR , KCNJ11 , PEX7 , POMC , and GCH1 mRNAs, further studies are needed to confirm the effect of the corresponding mutation on translational efficiency (Table 1).…”
Section: Uorfs and Human Diseasementioning
confidence: 99%
“…Additional uORF-altering mutations were identified by computational analysis of the Human Gene Mutation Database (7). Diseases with a confirmed implication of uORF mutations include Cystic fibrosis (CFTR) (63), the van der Woude syndrome (IRF6), hereditary pancreatitis (SPINK1), familial hypercholesterolemia (LDLR) and some others (7). Furthermore, the expression of the beta secretase BACE1, related to Alzheimer's disease (64), or the transmembrane receptor tyrosine kinase ERBB2, related to breast cancer (65), is at least partially controlled by uORFs.…”
Section: Medical Impactmentioning
confidence: 99%